Asphalt concrete moisture damage resistance: An evaluation of the coating ability of aggregates and binders - Peerapong Jitsangiam (2018)
© 2018 Trans Tech Publications, Switzerland. Moisture related damage is the single most significant issue facing asphalt pavements worldwide. The improvement of moisture damange resistance of asphalt concrete as a asphalt pavement surface is the way to enhance essential properties of the asphalt concrete mixture components between mix aggregate and a binder (asphalt cement) to withstand adverse effects from moisture. Moisture damage consists of two key mechanisms, the loss of adhesion between the binder and aggregate and the loss of cohesion within the asphalt contrete matrix. This research aims to investigate the adhesion mechanism through the use of the so-called rolling bottle test (RBT) to assess the binder coverage under moisture conditions. Through the use of Western Australian aggregates and Main Roads WA specific binders and adhesion agent, hydrated lime. The percentage coverage was assessed to determine the moisture sensitivity of the aggregate-binder interface. This method allows for a fundamental mechanism of moisture damage to be analysed from an inside out perspective, free of external influencing factors. The results from this study showed that different study aggregates yielded different levels of moisture damage resistance based on the results of RBTs, while the stiffer C320 binder showed greater adhesion to the both study aggregate types. The addition of hydrated lime significantly increased the percentage coverage all samples.